Consumption of Spa Tourism Products in the Slovak Republic and the Economic Results of Enterprises in the Spa Sector - Halenárová, Mária; Kubičková, Viera; Pekarovičová, Lenka; Čukanová, Miroslava (Konsumpcja produktów turystyki uzdrowiskowej w Republice Słowackiej i wyniki ekonomiczne przedsiębiorstw w sektorze uzdrowiskowym, 2025)
Aim: The aim was to identify the relationship between the proportion of self-paying and insured patients and the total revenues of spa facilities in Slovakia. Methodology: The analysis was based on data from the Statistical Office of the Slovak Republic and annual reports of spa enterprises for the period 2009-2023. The relationships between client structure and economic performance were evaluated using Pearson´s and Spearman´s correlation coefficients and simple linear regression. Results: The results show a strong and statistically significant correlation between the number of self-paying clients and the total revenues of spa enterprises. For the insured patients the relationship was weaker and statistically insignificant, indicating their stabilising but now growth-inducing role. The expenditure of public health insurance companies had a positive impact on the number of spa visitors, confirming their importance in maintaining demand. Implications and recommendations: The findings confirmed that self-paying clients play a key role in the economic sustainability of Slovak spas. For spa managers, this highlights the need for targeted marketing and product innovation for this segment. Policymakers should consider hybrid financing models that combine support for insured patients with incentives to attract self-paying clients. Originality/value: The paper fills a gap in the literature by providing quantitative evidence on the economic impact of spa tourism consumption in the Slovak Republic, using correlation and regression analysis to data rarely used in this context.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 4, s. 30-42
Keywords: tourism; spa; innovation; potential; turystyka; uzdrowisko; innowacja; potencjał